Stress Distribution Analysis of DKDT Tubular Joint in a Minimum Offshore Structure - Noviyanti, Irma; Prastianto, Rudi Walujo; Murdjito, Murdjito (Universitas Trunojoyo Madura, 2021)
A marginal field defines as an oil and/or gas field that has a short production period, low proven reservoir, and could not be exploited using existing technology. As the demand for oil and gas keeps increasing, one of the solutions to tackle the issues is to build the modified platform which came to be more minimalist to conduct the oil and gas production in the marginal field. Naturally, the minimum offshore structures are cost less but low in redundancy, therefore, pose more risks. Although the study on the minimum structures is still uncommon, there are opportunities to find innovative systems that need to have a further analysis toward such invention. Therefore, this study took the modified jacket platform as a minimum structure, and local stresses analysis by using finite element method is applied for the most critical tubular joint with multiplanarity of the joint is taking into account. The analysis was carried out using the finite element program of Salome Meca with three-dimensional solid elements are used to model the multiplanar joint. Various loading types of axial force, in-plane bending moment, and out-of-plane bending moment are applied respectively to investigate the stress distribution along the brace-chord intersection line of the tubular joint. The results show that the hotspot stress occurred at a different point along each brace-chord intersection line for each loading type. Finally, as compared to the in-plane bending moment or out-of-plane bending moment loading types, the axial force loading state is thought to generate greater hotspot stress.